Assessment of Interventions by Pharmacist in Improving Knowledge, Attitude and Practice towards Hypothyroidism among the Patients Attending at an Endocrine Clinic in Nepal - Maharjan, Sushma; Chhetri, Himal Paudel (Indian Journal of Pharmacy Practice)
Background: The diverse role of pharmacist for management of chronic disease carries significant effects. Hypothyroidism, common chronic endocrine disorders can affect multiple organs. So, educating patient can bring fluorescent in management of chronic disease like hypothyroidism. This study assessed the pharmacist provided intervention in hypothyroid patients in terms of knowledge, attitude and practice outcomes. Method: A prospective, case controlled, interventional based study with total 118 patients diagnosed with hypothyroid condition as the inclusion criteria. Knowledge, attitude and practice regarding hypothyroidism were assessed and recorded by using appropriately designed and validated standard questionnaire. Test group patients were counseled regarding hypothyroidism and provided with informative leaflet to them in local (Nepali) language. While in control group patients, no intervention was provided by pharmacist. After one month interval, knowledge, attitude and practice score were measured in both groups (test and control) by using same knowledge, attitude and Practice questionnaire. Effectiveness of counseling was evaluated in the test group by comparing mean scores of knowledge, attitude and practice before and after intervention using sampled paired t-test. Results: Mean knowledge, attitude and practice score of test group patients before intervention were 5.290 ± 3.043, 14.709 ± 1.540 and 2.677 ± 0.471 respectively and after intervention the score were 7.935 ± 2.231, 15 ± 1.201 and 2.935 ± 0.247 respectively (p value<0.05). Conclusion: Positive impact on patient's knowledge, attitude and practice towards disease management after intervention by pharmacist was observed.
Keywords: Attitude; Hypothyroidism; Knowledge; Practice score